2022
DOI: 10.1007/s15010-022-01794-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the seasonality of the respiratory syncytial virus during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has caused a variation in the circulation of common respiratory viruses. Our objective was to analyse the epidemiology of respiratory syncytial virus (RSV) bronchiolitis admissions during the COVID-19 pandemic in comparison with previous epidemic seasons. Methods We conducted an observational study involving infants with RSV bronchiolitis admitted to a tertiary hospital during two periods: pandemic COVID-19 (15 March 2020–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
(3 reference statements)
2
13
2
3
Order By: Relevance
“…We did not observe any outbreaks of RSV bronchiolitis during spring and summer 2021 (Fig. 1 ) or a higher percentage of prematurity and PICU admissions, as otherwise reported by other authors [ 6 ].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…We did not observe any outbreaks of RSV bronchiolitis during spring and summer 2021 (Fig. 1 ) or a higher percentage of prematurity and PICU admissions, as otherwise reported by other authors [ 6 ].…”
supporting
confidence: 86%
“…This prediction has come true in our area in autumn 2021, when school, kindergarten, and work social activities fully reprised. On the other hand, we have not observed any summer peak, as reported in Japan and Spain [ 5 , 6 ]. We fully agree with Bermúdez Barrezueta et al about the necessity of potentiating the epidemiological surveillance systems that control RSV circulation for a better management of health resources, including the better timing of palivizumab prophylaxis [ 6 ].…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In France, the 2020–2021 RSV season was characterized by a 3–4-month delay in the seasonal peak of RSV-associated hospitalizations 100 , 101 . Moreover, one Spanish hospital reported that RSV-associated bronchiolitis admissions were delayed until June 2021; in previous seasons, RSV-associated hospitalization peaks typically occurred between November and February 95 .…”
Section: Health Care Burden Of Non-sars-cov-2 Virusesmentioning
confidence: 99%
“…RSV is a non-segmented single negative strand RNA enveloped virus belonging to the Paramyxoviridae family, and is related to clinical pictures such as bronchiolitis, pneumonia, ashmatic bronchitis 3 . RSV is the most important virus responsible for hospitalization and even death in children under 5 years of age with acute lower respiratory tract infection (ALRI), especially in infants 4 , 5 .…”
mentioning
confidence: 99%